Perancangan Aplikasi Penjualan Dan Pembelian Pada Optik Merdeka Berbasis Visual Basic - Rosalina Yani Widiastuti (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2021)
Optik Merdeka is a privately owned agency located on Jalan Jenderal Gatot Subroto, Purwokerto. Optik Merdeka has an important role for the community as a service to buyers and management of sales and purchase transactions. Transaction management at Optik Merdeka still uses a simple manual system. So when inputting data one by one and if there is a calculation or input error, the process will start from the beginning again. With this problem, the author makes an application related to transaction management activities which consist of selling goods, buying and selling transactions. In making this application the author uses Visual Basic.NET and MySQL as the database.